Family policy with respect to large families in Visegrad countries - Bebel, Anna (Polityka rodzinna względem rodzin wielodzietnych w krajach Grupy Wyszehradzkiej, 2011)
The article presents the family policy aimed at the large families in Visegrad countries. The most important instruments in terms of supporting families with many children were compared. The conducted analysis showed that the country with the weakest family policy is Poland and that the largest amount of the help offered to large families is available in Hungary
Ekonomia = Economics, 2011, Nr 2 (14), s. 168-177
Keywords: Visegrad Group; family policy; large families